Self-Efficacy and Its Correlation With Reading Comprehension Of Senior High School Students - Apriliyani, Eka Putri; Usuludin, Moh. Ana (IREELL: Indonesian Review of English Education, Linguistics, and Literature, 2023)
Self-efficacy becomes one of psychological factor affecting successfully in doing some activities. By having self-efficacy, people can measure themselves in doing some tasks briefly. Self-efficacy is necessary because it influences people’s performance. Self-efficacy in reading comprehension is also called reading self-efficacy. The objective of this study is the researcher wants to know the correlation between self-efficacy and reading comprehension achievement of the eleventh grade Senior high School student. This study uses correlation quantitative research as a research design. The participant of the research was 179 students of eleventh grade of senior high school students in Indonesia. The instruments used were the reading test and self-efficacy questionnaire. For the reading test, the researcher adopted from TOEFL for Junior. Then, for self-efficacy questionnaire, the researcher adapted from MSLQ. The result showed that there was a very low correlation between self-efficacy and reading comprehension with a significance value was .020 and coefficient correlation of .174.